Sydowia polyspora dominates fungal communities carried by two Tomicus species in Pine plantations threatened by Fusarium circinatum - Munoz-Adalia, Jordan; Sanz-Ros, Antonio; Flores-Pacheco, Juan; Hantula, Jarkko; Diez, Julio; Vainio, Eeva; Fernandez, Mercedes (MDPI, 2017)
Bark beetles (Coleoptera, Scolytinae) carry a diverse filamentous fungal community sometimes acting as vectors or carriers of phytopathogens. In this study, mycobiota carried by two Tomicus species (Tomicus piniperda and Tomicus destruens) were investigated through (i) morphological and molecular identification of taxa; (ii) taxonomic richness, diversity, evenness, dominance and phoresy indices; (iii) ecological network analysis and (iv) statistical co-occurrence analysis. The studied mycobiota were formed by eleven taxa and showed a moderate fungal diversity with low evenness. The fungus Sydowia polyspora was significantly abundant and dominated the community. All the fungal taxa were randomly associated. Both insect species (T. piniperda and T. destruens) were collected from plantations of Pinus radiata infected by Fusarium circinatum. The ecological factors that could drive community ecology and phoretic links between fungi and bark beetles are discussed.
Keywords: Tomicus piniperda; Tomicus destruens; sienet; pystynävertäjä; kaarnakuoriaiset; fungi; bark beetles